The social power of the Bible in culture and politics. Issue 2 (March 2021) - Gent, Peter
Biblical texts hold social power, acting in and through the religious traditions that hold the Bible authoritative, with far-reaching impact on culture and politics. Work by Bruno Latour and others on the agency and action of artefacts provides a set of concepts that make possible analysis of how social power is delegated to the Bible and how the Bible in turn holds power over its readers and broader society. Tracing the action of the Bible in this way enables reflection on the performative impact of how the Bible is read and interpreted.